Krisis Keteladanan Kepemimpinan Gereja: Fondasi Gembala Sebagai Pemimpin Gereja Berdasarkan 1 Petrus 5:2-4 - Nicolas, Djone Georges; Manaroinsong, Tirza (Ridwan Institute, 2021)
President Jokowi as the supreme leader of the Republic of Indonesia on January 13, 2021, has set an example and at the same time proved his promise to make himself the first person to be injected with the Covid-19 Sinovac vaccine. Pastor leadership which is basically aimed at serving, caring for and fulfilling the needs of the congregation as sheep that have been entrusted by God is shifting direction and starting to lose its meaning. Because leadership has begun to be used as a leader's